The Akhlak Revolution: A Triadic Interplay Between Piety, Islamization, and Neoliberal Ethics - Amanulloh, Naeni; Huda, Muhammad Nurul; Maulidia, Hanifa (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
This article will examine the efforts of a group of middle-class urban Muslims in cultivating the piety. It will trace the working logic of the formation of pious subject, as a point of departure to comprehend the increasing of religious zeal of the middle-class urban Moslem. By exploration on the activity of the employee and leaders of a number of companies in the Santri Eksekutif program, we argue that the effort to be a pious subject is often related to and interplay with the aspirations of Islamization of public institutions and with neoliberal ethics. Furthermore, we argue that more than a quest for identity, religious expressions that are public are a form of requirement to be ethical and pious subjet. Through this article we aim to (1) describe a form of ethical and pious subject, (2) explore the formation process of the ethical and pious subject, and (3) accentuate the interplay and complex relationship between the process of cultivating piety, aspirations of Islamization of public institutions, and with neoliberal ethics. This article is based on ethnographic fieldwork in Jakarta and Bogor.